GEOGRAPHICAL DISTRIBUTION OF TOXIC ELEMENTS IN NORTHEAST MARMARA SEA SEDIMENTS AND ANALYSIS OF TOXIC ELEMENT POLLUTION BY VARIOUS POLLUTION INDEX METHODS (ISTANBUL/TURKEY) - Kam, E.; Yumun, Z. U. (ALOKI Applied Ecological Research and Forensic Inst Ltd, 2021)
In this study, the geographic distribution of toxic element concentrations was determined in Northeast Marmara Sea (Istanbul/Turkey) sediments. In addition, the pollution degree of the environment was analyzed using various pollution index methods. Geochemical analysis of 28 elements were performed in sediment samples. The concentrations of several elements (especially Fe, Mn, Ti, Zn, and Cr) were found to be very high in some locations. At sites, where heavy metal concentrations were high, foraminifera genera and species numbers and number of individuals were very low. The low number of foraminifera in the samples taken from some regions could be due to uncontrolled ship traffic and domestic and industrial discharges.
Keywords: marine sediments; elements; environmental index; pollution factors; eastern Marmara; Istanbul; geochemical analysis; HEAVY-METAL POLLUTION; SURFACE SEDIMENTS; TRACE-METAL; CONTAMINATION; GULF; FORAMINIFERA; MARINE; Environmental Sciences & Ecology